Two new endemic species of Bistriopelma (Araneae: Theraphosidae) from peru, including a new remarkable horned tarantula - Nicoletta, Micaela Mariel (2020)
The spider genus Bistriopelma Kaderka, 2015 is endemic to Peru and includes three species known to date: Bistriopelma lamasi Kaderka, 2015, B. matuskai Kaderka, 2015 and B. titicaca Kaderka, 2017. The present contribution diagnoses, describes and illustrates two new species of Bistriopelma from Peru: B. peyoi sp. nov. and B. kiwicha sp. nov., both based on male and female. The male of B. peyoi sp. nov. is provided with a remarkable thoracic horn, and the species is the first horned tarantula for this genus. An updated distribution map for all known species is presented.